Environmental and Human Health Implication of Oil Industry Pollution - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2021)
Oil pollution is not only a concern for the environment but also for human health. Contamination of air, water, and soil by wastes from the oil industry, whether as a consequence of acute or chronic events, constitutes an additional source of stress for organisms. Oil exploration and exploitation produces environmental hazards that are “slow poisons,” in that they often take months and years to cause disease and death. The widespread presence of constituents of crude oil in the bio-physical environment of the impacted communities is known to be capable of exerting some acute and long-term adverse health effects. In this issue, Al-Kharraz et al. report the incidence of various types of cancers, as well as kidney failure and respiratory diseases in human population affected by oil industry pollution. Material relief and immediate and long-term medical care are recommended to address the potential health effects of exposure to oil industry pollution.